Understanding Williams-Yulee v. The Florida Bar and its implications for freedom of speech in judicial elections. Issue 1 (3rd July 2018) - McLeod, Aman
ABSTRACT: This article discusses the US Supreme Court's 2015 decision in Williams - Yulee v. The Florida Bar and its potential implications for judicial candidate speech and judicial elections. Based in part on a survey of cases involving restrictions on judicial candidate speech decided before and after Williams - Yulee, the article argues that Williams - Yulee effectively overruled the Court's earlier decision in Republican Party of Minnesota v. White, by weakening the strict scrutiny test that White applied to judicial candidate speech regulations. Specifically, Williams - Yulee weakened White 's version of strict scrutiny by removing the demand that the government demonstrate the effectiveness of its speech-regulating policies in achieving its goals, and by embracing a more permissive form of inclusivity analysis. This weaker version of strict scrutiny could facilitate government interference in the public education process that occurs during judicial elections, which is a process that affects citizens' propensities to participate in elections, and their ability to make informed judgments about whom they want to put on the bench.